Is Additional Fluid Therapy Effective in the Treatment of Children with Urinary Tract Infection? - Yousefichaijan, Parsa; Sharafkhah, Mojtaba; Cyrus, Ali; Dorreh, Fatemeh; Arjmand, Ali (Journal of Pediatric Nephrology, 2016)
Introduction: Urinary tract infection can result in many complications such as abscess, hypertension, renal failure, renal scar, reflux, etc. Since there is no general agreement on the administration of additional fluid (1.5 times maintenance) for the early treatment of UTI, this study was conducted to evaluate the effect of additional fluid therapy. Materials and Methods: In This clinical trial study, 206 children with UTI who were admitted at Amir Kabir Hospital (Arak, Iran) from March 2012 to March 2013 were divided into two groups of 103. One group received the usual amount of maintenance fluid while the other group received 1.5 times more than usual maintenance. The course of the resolution of dysuria, frequency, malodorous urine, abdominal pain, and fever was compared between the two groups. Urine culture was performed for all patients 2, 7-10, and 90 days after admission. The patients were age and sex matched. The data was analyzed using descriptive statistics and the X2 method based on independent sample t-test. Results: Additional fluid had a significant effect on malodorous urine dysuria. However, it had an inverse effect on the treatment of fever and urinary frequency as it made them last longer. There was no difference in other parameters like abdominal pain and urine culture in 3 stages. Conclusions: Based on our study, the intake of excessive amounts of water has no significant effects on the results of the UTI treatment. However, due to lack of adequate evidence, further studies should be conducted in this field. Keywords: Urinary Tract Infection; Child; Fluid Therapy.